2022
DOI: 10.1002/ece3.9349
|View full text |Cite
|
Sign up to set email alerts
|

Phenology and plasticity can prevent adaptive clines in thermal tolerance across temperate mountains: The importance of the elevation‐time axis

Abstract: Critical thermal limits (CT max and CT min ) decrease with elevation, with greater change in CT min , and the risk to suffer heat and cold stress increasing at the gradient ends. A central prediction is that populations will adapt to the prevailing climatic conditions. Yet, reliable support for such expectation is scant because of the complexity of integrating phenotypic, molecular divergence and organism exposure. We examined intraspecific v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 158 publications
1
3
0
Order By: Relevance
“…However, it is apparent that our data did not support the CHV or the Climatic Extremes Hypotheses. The lack of a clear clinal variation in thermal tolerance limits in A. bipustulatus suggests conservatism of the thermal niche and is consistent with the findings of Gutiérrez-Pesquera et al (2022), which also found no relationship between thermal limits and elevation or temperature across populations of Rana parvipalmata tadpoles. In contrast, other studies have reported significant relationships between thermal tolerance traits and altitude within species of different terrestrial and semiaquatic taxa (e.g., salamanders and lizards - Trochet et al, 2018, frogs -Enriquez-Urzelai et al 2020or ants -Tonione et al 2020.…”
Section: Discusionsupporting
confidence: 87%
See 1 more Smart Citation
“…However, it is apparent that our data did not support the CHV or the Climatic Extremes Hypotheses. The lack of a clear clinal variation in thermal tolerance limits in A. bipustulatus suggests conservatism of the thermal niche and is consistent with the findings of Gutiérrez-Pesquera et al (2022), which also found no relationship between thermal limits and elevation or temperature across populations of Rana parvipalmata tadpoles. In contrast, other studies have reported significant relationships between thermal tolerance traits and altitude within species of different terrestrial and semiaquatic taxa (e.g., salamanders and lizards - Trochet et al, 2018, frogs -Enriquez-Urzelai et al 2020or ants -Tonione et al 2020.…”
Section: Discusionsupporting
confidence: 87%
“…Based on previous studies on the plasticity of thermal limits in freshwater taxa (e.g. Shah et al, 2017a;Gutiérrez-Pesquera et al, 2022) we also explore whether acclimation capacity is positively related with climatic variability across populations at different elevations, in agreement with the CVH.…”
Section: Introductionmentioning
confidence: 90%
“…As an adaptive response to larger seasonal differences in temperature, thermal tolerance and acclimation capacity of ectothermic species or populations tend to increase with increasing latitude from tropical through temperate climate zones (e.g., Cicchino et al., 2023; Deutsch et al., 2008; Peck et al., 2014; Rohr et al., 2018; Somero, 2005; Sunday et al., 2011; but see: Gunderson & Stillman, 2015; Sørensen et al., 2016) and from higher to lower elevations (Enriquez‐Urzelai et al., 2020; but not: Gutiérrez‐Pesquera et al., 2022; Sunday et al., 2019). This biogeographical pattern is consistent with the climate variability hypothesis (Ghalambor et al., 2006; Janzen, 1967), suggesting that climatic differences across altitudinal and latitudinal gradients lead to corresponding adaptations in thermal physiology (but see: Gutiérrez‐Pesquera et al., 2022). Low‐latitude species adapted to relatively stable temperature conditions may have a lower acclimation capacity and, therefore, may be more vulnerable to climate change (Sunday et al., 2014; Tewksbury et al., 2008; but see: Bovo et al., 2023).…”
Section: Introductionmentioning
confidence: 99%
“…As an adaptive response to larger seasonal differences in temperature, thermal tolerance and acclimation capacity of ectothermic species or populations tend to increase with increasing latitude from tropical through temperate climate zones (e.g., Somero 2005; Deutsch et al 2008; Sunday et al 2011; Peck et al 2014; Rohr et al 2018; Cicchino et al 2023; but see: Sørensen et al 2016; Gunderson & Stillman 2015) and from higher to lower elevations (Enriquez-Urzelai et al 2020; but not: Sunday et al 2019; Gutiérrez-Pesquera et al 2022). This biogeographical pattern is consistent with the climate variability hypothesis (Janzen 1967; Ghalambor et al 2006), suggesting that climatic differences across altitudinal and latitudinal gradients lead to corresponding adaptations in thermal physiology (but see: Gutiérrez-Pesquera et al 2022). Low-latitude species adapted to relatively stable temperature conditions may have a lower acclimation capacity and, therefore, may be more vulnerable to climate change (Tewksbury et al 2008; Sunday et al 2014; but see: Bovo et al 2023).…”
Section: Introductionmentioning
confidence: 99%